Hip-abductor fatigue influences sagittal plane ankle kinematics and shank muscle activity during a single-leg forward jump. (December 2018) - Gafner, Simone C.; Hoevel, Veronika; Punt, Ilona M.; Schmid, Stefan; Armand, Stephane; Allet, Lara
Abstract: Diminished hip abductor strength decreases postural control which is a parameter that is associated with an increased risk of ankle sprains. In our study we evaluated the influence of hip abductor fatigue on sagittal plane ankle kinematics and shank muscle activity during a single-leg forward jump. Sagittal ankle plane kinematics are important in ankle sprains but less studied than frontal plane kinematics. Therefore, we evaluated differences in sagittal ankle kinematics (12-camera motion capture system) and lower limb surface electromyographic muscle activity in 20 healthy, recreationally active adults (9 females, 11 males, mean age 30.3 SD 4.0 years, mean BMI 23.6 SD 2.8 kg/m 2 ) before and after a hip abductor fatigue protocol (200-ms prior, at and in the 250-ms following initial contact (IC)). After fatigue, the maximal ankle plantar-flexion angle decreased prior to IC (median 3.8° [interquartile range 0.1, 7.2], p = 0.014), at IC (4.1° [−0.3, 5.0], p = 0.027) and post IC (4.1° [−1.3, 5.0] p = 0.036). Gastrocnemius activity onset was delayed (−28.0 ms [−44.0, 0.0], p < 0.01). Average activity of the tibialis anterior increased prior to IC (pre-fatigue 19.32% [14.89, 33.45], post-fatigue 28.95% [18.49, 34.81], p < 0.05). Hip-abductor fatigue influenced sagittal ankle kinematics and shank muscle activity during single-leg landings.